The early retinal progenitor-expressed gene Sox11 regulates the timing of the differentiation of retinal cells. - Sock, Elisabeth; Wegner, Michael; et al. (Development, 2013)
Sry-related HMG box (Sox) proteins, Sox11 and Sox4 are members of the SoxC subtype. We found that Sox11 was strongly expressed in early retinal progenitor cells and that Sox4 expression began around birth, when expression of Sox11 subsided. To analyze the roles of Sox11 and Sox4 in retinal development, we perturbed their expression patterns in retinal explant cultures. Overexpression of Sox11 and Sox4 in retinal progenitors resulted in similar phenotypes: an increased number of cone cells and dramatically decreased numbers of rod cells and Müller glia. Birth-date analysis showed that cone cells were produced at a later developmental stage than that in which cone genesis normally occurs. Sox11-knockout retinas showed delayed onset and progress of differentiation of subsets of retinal cells during the embryonic period. After birth, retinal differentiation took place relatively normally, probably because of the redundant activity of Sox4, which starts to be expressed around birth. Overexpression and loss-of-function analysis failed to provide any evidence that Sox11 and Sox4 directly regulate the transcription of genes crucial to the differentiation of subsets of retinal cells. However, histone H3 acetylation of some early proneural genes was reduced in knockout retina. Thus, Sox11 may create an epigenetic state that helps to establish the competency to differentiate. Taking our findings together, we propose that the sequential expression of Sox11 and Sox4 during retinogenesis leads to the fine adjustment of retinal differentiation by helping to establish the competency of retinal progenitors. © 2013.
UnivIS-Import:2015-03-09:Pub.2013.med.IB.LPCIPDBI.theear
Keywords: Mouse; Progenitor cells; Retina; Sox family transcription factor